An equilibrium search model of the labor market entry of second-generation immigrants and ethnic danes - Nabanita Datta Gupta; Lene Kromann (Institute for the Study of Labor (IZA), 2013)
Using a search model for Danish labor market entrants, we are one of the first studies to test whether second-generation immigrants have the same job-offer arrival and layoff rates as ethnic Danes have. We contribute to the search literature by incorporating matching as a way to ensure sub-sample homogeneity. Thus, we match second-generation immigrants to their ethnic Danish twins on the basis of parental characteristics and informal network quality. There are big differences before matching, but after matching, second-generation immigrants perform as well or better than their ethnic Dane counterparts do on the labor market, though not with respect to layoffs. This result is mainly driven by the group of high school graduates and those with a primary school education only. Second generation immigrants with vocational education, males in particular, face both significantly lower arrival rates when unemployed and significantly higher layoff rates than those of their ethnic Danish twins.
Keywords: J15; J61; J71; 330; firm behavior; equilibrium search model; matching; second-generation immigrants